Effect of an intervention of emotional intelligence concerning psychological well-being and depression on older adults - Segura Barrera, Ariadna Pamela (Consorcio de Universidades Mexicanas A.C., 2019)
A workshop on integrative emotional intelligence (EI) was implemented, which included Rational Behavioral Emotional Therapy techniques in congruence with Salovey and Mayer’s model of four branches. The objective of this study was the evaluation of the effect of the workshop on EI on the levels of psychological well-being (PWB) and depression in older adults. The instruments used were the EI Self-Report Scale, the Beck-II Depression Inventory and the PWB scale. The workshop’s effect size on the dependent variables (knowing the causality of intrapersonal emotions and explaining sensations derived intra- and interpersonally) was calculated using the Wilcoxon Rank-Sum Test. There wasn’t a significant difference in PWB. However, some participants showed a reduced level of depression.